Pengurangan Subsidi BBM dan Polusi Udara Melalui Kebijakan Program Konversi dari BBM ke BBG Untuk Kendaraan di Propinsi Jawa Barat - Vita Susanti; Agus Hartanto; Ridwan Arief Subekti; Hendri Maja Saputra; Estiko Rijanto; Abdul Hapid (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2010)
The  number  of  vehicle  that  use  oil  (BBM)  is  increasing  every  year  in  Indonesia  while  national  oil  reserve become smaller, so that the oil should be imported. The impact of using oil are increasing subsidy and air pollution.  Thus, it is now becoming important to replace oil with another environmentally friendly energy, one of them is gas (BBG). Based on the number of vehicle and infrastructure in gas pipeline, part of northern West Java potentially can  be  chosen  for  the  implementation  of  conversion  program  to  gas  (BBG).  The number  of  vehicle  in  potential regions  such  as  Depok,  Cibinong,  Bogor,  Bekasi,  Cikarang,  Karawang,  Purwakarta,  Cirebon,  and  Bandung  are around 875,505 units. From these data, we simulated the potential profit to be gained each year by converting 10% for the first year and increasing it to 5% for every year. By investing 3.16 trillion for conversion, 14.9 trillion can be achieved in  the  form  of  fuel  subsidy  savings.  In  addition,  emission  reduction  converted  to  a  CDM  (clean development  mechanism)  can  become  local  revenues.  Total CDM generated during 5 years predicted is of U.S $ 772,385. From this study, it can be concluded that converting oil (BBM) to gas (BBG) is highly beneficial.